Analisis Perhitungan Volume Beton Metode Konvensional dan BIM Autodesk Revit pada Proyek Jembatan Tipe Lengkung terhadap Efektivitas Biaya - Alkhansa Auliya Dzakiyyah; Lusiana Lusiana; Rafie Rafie (Pusat riset dan Inovasi Nasional, 2026)
Concrete volume calculation is a crucial factor in preventing cost overruns when preparing the Budget Plan (RAB) for construction projects. In arch bridge projects, the complex structural geometry often makes conventional volume calculation methods complicated and prone to errors, particularly due to the geometric complexity of the arch beams. This study aims to analyze the comparison of concrete volume calculation results between the conventional method and the Building Information Modeling (BIM) method using Autodesk Revit in terms of cost-effectiveness. The case study was conducted on the Short Span II Pulau Balang Bridge Duplication Project in the Nusantara Capital City (IKN), Penajam Paser Utara Regency, East Kalimantan. The research objects include substructures (bore piles, pile caps, abutments, piers, and wing walls) and superstructures in the form of arch beams. The research method employs a quantitative approach by calculating concrete volumes conventionally using AutoCAD and Microsoft Excel, as well as calculating with BIM Autodesk Revit through three-dimensional modeling and Quantity Take-Off (QTO) exports. The results indicate that the BIM Autodesk Revit method generates a larger concrete volume compared to the conventional method, resulting in a higher total cost based on the BIM volume. The total cost for the conventional method amounted to IDR 142,613,245,996.12, while the BIM Autodesk Revit method amounted to IDR 143,127,208,186.60. These differences are influenced by the level of calculation detail, the simplification of shapes in the conventional method, and the precision of modeling in Autodesk Revit.